The effect of neonatal intensive care unit orientation program on decreasing the anxiety of premature infants' mothers - Aazam Heidarzadeh; Zeinab Taheri; Mahlagha Dehghan; Mansooreh Azizadeh-Forouzi; Ali Akbari (Tehran University of Medical Sciences, 2016)
Background & Aim: High levels of anxiety in mothers after the birth of a premature infant and its negative effects and consequences on the infant and the family indicate the necessity of performing an intervention for them. This study was conducted to evaluate the effect of neonatal intensive care unit orientation program on the anxiety of premature infants' mothers in Shahrekord. Methods & Materials: In this semi-experimental non-equivalent controlled study which was conducted in 2015, 64 mothers of premature infants were enrolled who were allocated into two groups of control and intervention. Participants of the intervention group participated in three 30-minute face-to-face unit orientation educational program. Data were gathered using the Spielberger's State-Trait Anxiety Inventory that has 40 questions and were analyzed using central indices, dispersion, Kolmogorov-Smirnov test, Chi square, Fisher's exact test, independent t-test and Mann-Whitney test. Results: The mean score of anxiety of the mothers had no significant difference between the control group (102.16 ± 4.72) and the intervention group (100.12 ± 1.66) before the intervention (p > 0.05). The mean score of both groups still had no significant difference after the intervention (p > 0.05). Also comparing the mean score of the trait anxiety and the situational anxiety subgroups between both groups before and after the intervention showed no significant difference (p > 0.05). Conclusion: Considering the ineffectiveness of the neonatal intensive care unit orientation program on the anxiety of mothers, it seems that this method could not decrease mothers' anxiety on its own. Therefore it is necessary to evaluate the effect of other interventions on the anxiety of premature infants' mothers in future studies.